Marital satisfaction in Iranian infertile women: A systematic review and meta-analysis - Amir Tabatabaee; Arezoo Fallahi; Bahre Shakeri; Vajiheh Baghi; Reza Ghanei Gheshlagh (Frontiers Media S.A., 2022)
BackgroundInfertility is a severe crisis in life that, in addition to creating psychological problems and disrupting a parent's identity and role, negatively impacts couples' marital satisfaction. Different studies in this field have reported different results, so this systematic review and meta-analysis was conducted to estimate the marital satisfaction standard score among infertile Iranian women.MethodThe databases of PubMed, Scopus, Web of Science, Embase, Scientific Information Database, and MagIran were searched without a time limit. We used the meta-analysis and a random-effects model to estimate the marital satisfaction pooled score. The heterogeneity of studies was examined with the I2 index and Cochrane's Q test. The correlation between the pooled score with the publication year and the mean age of women was evaluated using meta-regression. We assessed the publication bias by the Egger test.ResultsSeventeen studies with a sample size of 2,421 people were analyzed. The marital satisfaction pooled score of infertile women was 49% (95% CI: 39-60%). The marital satisfaction score in region 1 of the country (54, 95% CI: 42.7-65.3%) was higher than in other regions (45, 95% CI: 40-58%). Also, the marital satisfaction pooled score based on the Enrich scale (54, 95% CI: 39-69%) was higher than the score reported on other scales (45, 95% CI: 29-61%). Publication bias was not significant.ConclusionInfertile women have moderate to low marital satisfaction, rooted in the culture and context of Iranian society. It seems necessary to provide measures to strengthen marital satisfaction, strengthen family relationships and prevent family disintegration in these women.